Reformulasi Nilai-Nilai Pancasila sebagai Pijakan Berbangsa - Syihabul Furqon (UIN Sunan Gunung Djati Bandung, 2021)
This book is part of Yudi Latif's anxiety as a child of the nation to respond to the problems of the nation and state today. In addition to presenting a description of the Pancasila philosophy as the focus, this book also aims to formulate state problems through studying the fundamental and essential perspective of the Unitary State of the Republic of Indonesia, namely Pancasila. In this book, it is as if Yudi wants a precise formulation for the decline of the nation's character because for him this decline has become cancer, not the flu anymore. Therefore, through Pancasila as an idea and a practice, Yudi wants to find and at the same time seek answers to why the problems of Indonesia as a country and a nation are still recurring. Yudi wants this nation to have a new political vision, a vision that is a solution to the crisis of morality and ethos that has hit the nation. For Yudi, Pancasila is a